Percepções docentes e formulação de Política Pública de Educação Ambiental no município de Capivari (SP). - Angelim, Karen Bertoldo (Universidade Federal de São Carlos, 2026)
Environmental Education has been the subject of research and legislation due to the importance and scope of environmental issues. It is a fact that the environment has become a global concern, whether due to climate change and extreme events, deforestation and pollution, among other factors. Since 1997, through the National Curriculum Parameters (PCN), the environment has been addressed in the classroom as a cross-cutting theme. From that period onward, legislation related to the topic has been updated, and Environmental Education has gradually gained prominence and recognition. In this context, understanding how teachers perceive the environment and how they incorporate Environmental Education topics into their classes is of vital importance for advancing toward a more environmentally responsible society, committed to environmental issues and socio-environmental justice. This project proposed a study with teachers from the municipal school system of Capivari (SP), using interviews, questionnaires, and documentary research, in order to investigate their environmental perceptions, how they develop environmental themes in the classroom, and how public authorities could contribute to this process. The research has a qualitative approach, and data analysis was carried out using Content Analysis, according to Bardin.
Teachers’ perceptions and the formulation of Public Environmental Education Policy in the municipality of Capivari (SP).
Keywords: Educação ambiental; Percepção ambiental; Políticas públicas; Environmental education; Environmental perception; Public policies; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade; 11. Cidades e Comunidades Sustentáveis; 12. Consumo e Produção Responsáveis; 14. Vida na Água; 15. Vida Terrestre